St. Ludwig Monastery in Vlodrop (Bulletin KNOB, 2003)
The local-history association Heemkundevereniging Roerstreek (HVR) and the St. Ludwig citizens' committee, with support from various other associations including the Cuypers society, have campaigned for the conservation of St. Ludwig College in the municipality of Roerdalen for years.St. Ludwig College in Vlodrop was founded by Franciscans from the Saxon province. Just as many other religious groups in 1875 they were forced to suspend their activities in Germany. The priests bought a site in the province of Limburg.Between 1905 and 1909 an enormous school/monastery complex was built in Vlodrop. The monastic order focused exclusively on education to German pupils. In 1926 the boarding school was recognised as a Gymnasium Deutsche Schule im Ausland by the German government.Because of the decrease in the number of vocations and pupils the boarding school was closed on 1 October 1978. In 1984 the building was sold to the Education and Science of Creative Intelligence Organisation, a branch of the Maharishi organisation.Shortly after the Maharishi had settled in Vlodrop, research was started within the scope of the Monuments Inventory Project. The St. Ludwig College proved to be a valuable building, dating from an exceptional period, the period of the Kulturkampf.The Maharishi and his organisation did not have an interest in any historical research into the building. The municipality and the province took the position that the arrival of the Maharishi European Research University (MERU) meant an incentive to employment in the region. Both the government and the province granted subsidies to realise this economic interest.However, any significant economic interest for the environment failed to take place. In October 1996 the Maharishi announced that he wanted to demolish the monastery complex because its building style, the character of the materials used and particularly the orientation of the building did not at all match the wishes of his organisation. In addition, there was the threat that the MERU would disappear from Vlodrop if the monastery complex was not demolished.Since 1996 a new 'cultural dispute' has arisen. The conservation of a monumental complex which, in defiance of all the rules, is being gradually dismantled by the Maharishi organisation, is the issue of an almost inextricable tangle of legal proceedings.